Phytochromes and Shade-avoidance Responses in Plants - FRANKLIN, KEARA A. (Ann Bot, 2005)
• Background and Aims The ability to detect and respond to the impending threat of shade can confer significant selective advantage to plants growing in natural communities. This Botanical Briefing highlights (a) the regulation of shade-avoidance responses by endogenous and exogenous factors and (b) current understanding of the molecular components involved in red to far-red ratio signal transduction. • Scope The Briefing covers: (a) the shade-avoidance syndrome in higher plants; (b) the adaptive significance of shade avoidance in natural light environments; (c) phytochrome regulation of shade-avoidance responses; (d) the role of blue light signals in shade avoidance; (e) gating of rapid shade-avoidance responses by the circadian clock; (f) potential signalling components and future perspectives.